Uso de sistema computacional e análise morfológica para identificação de unidades de dispersão de espécies invasoras - Jardim, Loraine Rodrigues (2012)
The occurrence of invasive plants can alter crop yields, because these plants often grow so strong, competing for light, water and nutrients, affecting seed production. The taxonomic identification of these species is the first step in planning a control program. The objectives of this work are: develop and validate a computer system to support the identification of units spread of invasive species; differentiate seeds of three species of quarantine pests Amaranthus genus of three species of the same genus harmful tolerated by analyzing the morphology inside and outside of their seeds. This work is organized into two chapters: Chapter 1 - describes the process of building a computer system to support the identification of units spread of invasive species. The database of the computer system was composed of morphological descriptions, drawings and photographs of the morphological structures of 198 seeds of invasive species. We developed a tool (available on the Web) to use the database built, providing morphological search by entering information on the morphology of seed and/or dispersion unit that seeks to identify the user. We conducted a test system functionality, which consisted of a questionnaire assessment while using the system. The system proved effective in identifying species, aiding the identification of invasive species. The creation of the database with the information and proposed structure meets the demand of the identification system. Chapter 2 - presents the morphological differentiation of the seeds of six species of the genus Amaranthus, seeking to differentiate species of harmful species quarantine pests in Brazil. We analyzed morphological descriptions of six species of the genus Amaranthus produced and a dichotomous key to highlight morphological able to differentiate species. The visualization of the structure of the embryo by slitting the seed, allows to differentiate the species of Amaranthus. Detailed analysis of the morphological internal and external seeds of Amaranthus is effective in the identification and differentiation of species.